Saúde Ocupacional no setor industrial: um estudo acerca do programa de conservação auditiva de uma companhia siderúrgica - Santos Filho, Francisco Assis dos (2021)
The steel industry is made up of a wide variety of industrial processes, which present different occupational risks to worker health, including noise and other adjuvant factors. This reality gives the steel industry the peculiarity of concentrating the most varied chemical and physical risks in a single plant, highlighting the complexity of occupational health management, including with regard to hearing loss. In this context, a steel company, the object of this study, is included. Given this reality, this research aims to evaluate how the hearing conservation program is configured in a large steel plant. The degree of implementation of the Hearing Conservation Program (HCP) was assessed in terms of structure and processes, using indicators validated from questionnaires answered by managers, whose focus is process management. This is a study of a qualitative-quantitative and descriptive nature regarding the purposes. As for the techniques used, it is a documentary and field study. Primary and secondary data were collected and treated using content analysis and descriptive statistics techniques. Ten occupational health managers who make up the company's SESMT (Specialized Service in Safety Engineering and Occupational Medicine) participated in the study. The assessment of the degree of implementation identified key points regarding limitations and improvements towards improving the program, characterizing itself as an advance in the systematization of activities related to HCP in organizations.